Activation of UPR Signaling Pathway is Associated With the Malignant Progression and Poor Prognosis in Prostate Cancer. Issue 3 (8th October 2016) - Liu, Junnan; Xiao, Maolin; Li, Jianjun; Wang, Delin; He, Yunfeng; He, Jiang; Gao, Fei; Mai, Li; Li, Ying; Liang, Yong; Liu, Yuejiang; Zhong, Xiaoni
Abstract : BACKGROUND: Currently, the role of UPR signaling in prostate cancer (PCa) is unclear. To evaluate the relationship between UPR signaling pathway and the prognosis of PCa, we explored the expression of IRE1, PERK, and ATF6 in tissues. METHODS: A total of 160 PCa and 30 benign prostate hyperplasia (BPH) tissues were collected. The expression of UPR signaling factors was assessed by immunohistochemistry. The staining characteristics were identified and evaluated for associations with clinicopathologic parameters, PSA recurrence survival, and prostate cancer‐specific morality. RESULTS: The expressions of ATF6α, PERK, and IRE1α were significantly associated with Gleason grade, PSA level, T stages and M stage, while this association was not significant in N stage. Additionally, UPR signaling factors expressed correlatively with each other. In further studies, high expression level of UPR signaling factors was usually detected in patients who suffered poor prognosis. Patients with positive UPR signaling factors meet shorter survival duration both on cancer‐specific morality and PSA recurrence. Multivariate analysis showed that IRE1α (HR = 4.461 95%CI = 1.270–15.670 P  = 0.020) could be a potential factor in predicting PSA recurrence independently. CONCLUSIONS: UPR signaling factors were co‐activated and activation of UPR signaling was implicated to the malignant progression and worse prognosis of PCa. The mechanism and function of UPR signaling in PCa are still to be determined. Prostate 77:274–281, 2017 . © 2016 Wiley Periodicals, Inc.